2007 IEEE Sensors 2007
DOI: 10.1109/icsens.2007.4388409
|View full text |Cite
|
Sign up to set email alerts
|

3D Modeling and Simulation of SH-SAW Devices Using the Finite Element Method

Abstract: Shear Horizontal Surface Acoustic Wave (SH-SAW) devices have been extensively used in chemical and biosensing applications mainly because these waves are not attenuated in liquid media like Rayleigh waves. It is extremely important to model and simulate the device prior to its actual fabrication in order to gain a better understanding of the device performance and optimizing its design parameters. This paper presents the 3-dimensional Finite Element (FE) modeling and simulation results for a SH-SAW device usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Unlike other numerical methods, the FEM can model device characteristics using predefined boundary conditions, which make this method more versatile. Previous studies [21,22,[25][26][27] have reported an FEM analysis technique which utilized the voltage of the output IDT of a SAW device to predict its frequency response. The results indicated that three-dimensional (3D) FEM simulations were needed to accurately predict the frequency response of the fabricated device, however at the cost of using more computational resources than two-dimensional (2D) models [25,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other numerical methods, the FEM can model device characteristics using predefined boundary conditions, which make this method more versatile. Previous studies [21,22,[25][26][27] have reported an FEM analysis technique which utilized the voltage of the output IDT of a SAW device to predict its frequency response. The results indicated that three-dimensional (3D) FEM simulations were needed to accurately predict the frequency response of the fabricated device, however at the cost of using more computational resources than two-dimensional (2D) models [25,28,29].…”
Section: Introductionmentioning
confidence: 99%